1977
DOI: 10.1507/endocrj1954.24.277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LATS, TSH and cholera toxin on the thyroid gland in nude mice.

Abstract: SynopsisThree thyroid stimulators; LATS, TSH, and cholera toxin, have been tested by bioassay using congenitally athymic homozygous mice (nu/nu), nude mice and control littermates (nu/+) possessing normal thymic function. nu/+ Animals showed a response to LATS similarly to normal white mice of the ddN strain. The assay response to LATS in nu/nu animals was about half that in normal mice. TSH also showed a less stimulating action in nude mice.Cholera toxin made a long acting response similarly to LATS. The resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Mullin et al (1976) reported that cholera toxin stimulated adenyl cyclase and also bound with the same receptor of TSH in the thyroid. In the previous paper we demonstrated the thyroid stimulating action of cholera toxin (Ochi et al, 1977) and in the present experiment we confirmed an evidence for the binding of both cholera toxin and TSH to the same receptor.…”
Section: Discussionsupporting
confidence: 89%
“…Mullin et al (1976) reported that cholera toxin stimulated adenyl cyclase and also bound with the same receptor of TSH in the thyroid. In the previous paper we demonstrated the thyroid stimulating action of cholera toxin (Ochi et al, 1977) and in the present experiment we confirmed an evidence for the binding of both cholera toxin and TSH to the same receptor.…”
Section: Discussionsupporting
confidence: 89%
“…TSAb assay and TSBAb assay using porcine thyroid cells were performed as previously described (11). T4 production activity using mouse bioassay was measured according to the method of McKenzie as previously described (12). Test sera Sera from Graves' disease with abnormally negative TRAb activity (untreated and during treatment) were used.…”
mentioning
confidence: 99%
“…TR-ab activity was expressed as bTSH amounts diluted with pooled normal human serum (bTSH equiv¬ alents in 0.05 ml of test serum). LATS activity was mea¬ sured as previously described (25). Thyroid-stimulating activity of TS-ab and TSH-blocking activity of TSB-ab were assayed by cAMP production using cultured porcine thyroid cells (26).…”
Section: Radioreceptor Assaymentioning
confidence: 99%